2011
DOI: 10.1103/physrevd.84.045022
|View full text |Cite
|
Sign up to set email alerts
|

The two-loop hemisphere soft function

Abstract: The hemisphere soft function is calculated to order α 2 s . This is the first multi-scale soft function calculated to two loops. The renormalization scale dependence of the result agrees exactly with the prediction from effective field theory. This fixes the unknown coefficients of the singular parts of the two-loop thrust and heavy-jet mass distributions. There are four such coefficients, for 2 event shapes and 2 color structures, which are shown to be in excellent agreement with previous numerical extraction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
220
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(234 citation statements)
references
References 52 publications
14
220
0
Order By: Relevance
“…To understand these techniques in the context of searches for new phenomena, the jet mass must be well-modeled through leading-order (LO) or next-toleading-order (NLO) Monte Carlo (MC) simulations. Much recent theoretical work in QCD has focused on the computation of jet mass, including predictions using advances in an effective field theory of jets (soft collinear effective theory, SCET) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Studies of the kind reported in the present analysis can provide an understanding of the extent to which MC simulations that match matrix-element partons with parton showers can model the observed internal jet structure.…”
Section: Jhep05(2013)090mentioning
confidence: 99%
“…To understand these techniques in the context of searches for new phenomena, the jet mass must be well-modeled through leading-order (LO) or next-toleading-order (NLO) Monte Carlo (MC) simulations. Much recent theoretical work in QCD has focused on the computation of jet mass, including predictions using advances in an effective field theory of jets (soft collinear effective theory, SCET) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Studies of the kind reported in the present analysis can provide an understanding of the extent to which MC simulations that match matrix-element partons with parton showers can model the observed internal jet structure.…”
Section: Jhep05(2013)090mentioning
confidence: 99%
“…Among the mixed virtual-real and double real emissions, only the diagrams in Figure 3 give nonvanishing contributions. The same matrix elements also arise in other two-loop computations of soft functions [24][25][26][27][28][29][30][31][32], what makes our case different are the phase-space constraints and the necessity of working with an additional analytic regulator. In the following, we denote the individual contributions of these diagrams to the soft function by…”
Section: Setup Of the Calculationmentioning
confidence: 99%
“…[69,70]. The corresponding two-loop soft functions are also known for zero-jettiness [71,72] and for general Njettiness [73]. The first process calculated at NNLO using this method was pp → W +jet [16], followed by calculations of the pp → Higgs+jet [8] and pp → Z +jet [18] processes, and by detailed phenomenological studies of these processes at this order [74][75][76].…”
Section: Introductionmentioning
confidence: 99%